Association between Self-Medication Behavior and Adherence among Medical Students in Dhaka, Bangladesh (Asian Journal of Pharmaceutics (AJP), 2017)
Background: Self-medication practice poses a positive impact when adequate patient adherence exists. As medical students commonly self-medicate, the aim is to find association between self-medication behavior and adherence among medical students in a private medical college in Dhaka, Bangladesh. Materials and Methods: This descriptive cross-sectional study was conducted among 204 medical students of Dr. Sirajul Islam Medical College, Dhaka, from October to December 2016. A pre-designed and pre-tested questionnaire was used for data collection. Data were analyzed using Microsoft Excel 2003 for counts and percentages. Association between self-medication behavior and adherence was assessed using Chi-square test. The statistical significance was set at P ≤ 0.05. Results: Students practising self-medication was 81.4%, and prevalence was more among 3rd year students. Students obtained drug information from pharmacy retailers, and pharmacy was the main source for obtaining drugs without a prescription. Fever and headache (83.1%) were the most frequently reported illness. Commonly used drugs were antipyretics and analgesics among all students. Reasons for self-medication were minor ailments and quick relief. Adherence among 204 students was observed as, only 5.4% students never forget to take medicines, 18.6% do not change the dose, frequency or course duration, and 2.9% do not discontinue treatment without doctor’s advice. 28.4% take doctor’s advice when symptoms persist and 20.6% when adverse effects occur. There was a significant association of self-medication practice and adherence among students (P < 0.05). Conclusion: High prevalence of self-medication exists among medical students associated with low level of adherence. Students must be educated about improvement of adherence to benefit from self-medication.